2017
DOI: 10.1177/1010428317692234
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia microvesicles affect healthy hematopoietic stem cells

Abstract: Microvesicles are released by different cell types and shuttle mRNAs and microRNAs which have the possibility to transfer genetic information to a target cell and alter its function. Acute myeloid leukemia is a malignant disorder, and leukemic cells occupy all the bone marrow microenvironment. In this study, we investigate the effect of leukemia microvesicles on healthy umbilical cord blood hematopoietic stem cells to find evidence of cell information transferring. Leukemia microvesicles were isolated from acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The underlying mechanism(s) are various, and sometimes contradictory. In fact, MVs are capable of stimulating tumor cell proliferation, 24 inducing angiogenesis, 20,28 suppressing normal cell development, 21,29,30 modulating tumor/microenvironment interactions 31 and inhibiting anti-tumor immune response. 17,22,32 The role of MVs in the context of human MM is now being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism(s) are various, and sometimes contradictory. In fact, MVs are capable of stimulating tumor cell proliferation, 24 inducing angiogenesis, 20,28 suppressing normal cell development, 21,29,30 modulating tumor/microenvironment interactions 31 and inhibiting anti-tumor immune response. 17,22,32 The role of MVs in the context of human MM is now being investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 14 On the other hand, one study showed that AML EVs increased the number of HSCs by enhancing their survival while retaining their clonogenicity and stemness with no change in the hematopoietic CD34 + , CD34 + CD38 − , CD90 + , and CD117 + phenotypes. 67 Illustrating one of the key challenges in understanding HSPC regulation by EVs, neither of the two latter studies identified the specific EV component responsible. We and others previously showed that EVs released by steady-state or reprogrammed malignant stroma carry cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect of leukemic BM cell‐derived MVs was seen on healthy UCB‐derived HSCs. Although increased levels of the oncomir miRNA‐21 and miRNA‐29a genes were observed in the treated HSCs, the colony‐forming ability was retained and high ranges of CD34 + , CD34 + CD38 − , CD90 + , and CD117 + phenotypes were perceived as signs of stemness (Razmkhah et al, 2017).…”
Section: Role Of Evs In Hematopoiesis/hematological Malignanciesmentioning
confidence: 99%